2017
DOI: 10.1016/j.hpb.2017.02.438
|View full text |Cite
|
Sign up to set email alerts
|

Splenic vein reconstruction is unnecessary in pancreatoduodenectomy combined with resection of the superior mesenteric vein–portal vein confluence according to short-term outcomes

Abstract: SMPVrPD without SV reconstruction can be safely conducted. Additionally, preservation of these two confluences may reduce the risk of LSPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
0
33
2
2
Order By: Relevance
“…Some have considered reconstructing the SpV to prevent LPH. Although there have been reports that it is important to preserve the flow of the LGV and MCV directly into the PV-SMV when SpV reconstruction is unnecessary [1][2][3], it may not be possible when tumor invasion necessitates resection, as in this case. There is also a report that the simultaneous resection of the splenic artery can prevent the occurrence of varices due to LPH, but in this case, there was a risk of severe complications such as splenic infarction and residual gastric blood flow disorder [7].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some have considered reconstructing the SpV to prevent LPH. Although there have been reports that it is important to preserve the flow of the LGV and MCV directly into the PV-SMV when SpV reconstruction is unnecessary [1][2][3], it may not be possible when tumor invasion necessitates resection, as in this case. There is also a report that the simultaneous resection of the splenic artery can prevent the occurrence of varices due to LPH, but in this case, there was a risk of severe complications such as splenic infarction and residual gastric blood flow disorder [7].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, there may be another route from the SpV to the SMV and/or PV via the IMV via the marginal vein of the left-sided or transverse colon and/or the right-sided colon, which may cause colonic varices [7]. In addition to these four routes, there are two non-varicose routes: splenic-colonic collateral circulation (arc of Barkow) and physiological splenic renal shunt [1]. Regarding the incidence of colonic varices, a previous study involving 43 cases that underwent PD with PVR reported that colonic varices developed in 27 cases (63%) and 3 cases required treatment [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the gastric drainage veins should be determined by preoperative computed tomography angiography and intraoperative inspection. The importance of preservation of the LGV or RGEV has been emphasized in previous reports. Preoperative or intraoperative planning for preservation of the gastric drainage veins is important when TP is performed.…”
Section: Discussionmentioning
confidence: 96%
“…Аналогичные результаты были получены в исследовании H. Tanaka и соавт. [15]. Профилактика послеоперационного панкреатита при резекционных операциях на ПЖ в первую очередь в случаях, сопряженных с резекцией вен, является обязательным компонентом периоперационного ведения больных.…”
Section: рис 3 кривая каплана-майера выживаемость больных после хиunclassified